Promising but still uncertain steps towards better prediction of functional outcome in ICU patients - Bos, Lieuwe D.; Schouten, Laura R.; Schultz, Marcus J. (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
In a recent publication on their ‘Towards RECOVER’ study, an ongoing multicenter project evaluating patient and caregiver outcomes after prolonged mechanical ventilation, Herridge et al. report on functional outcome up to one year after discharge in patients who needed support in an intensive care unit (ICU) for more than one week (1). For this, the ‘Towards RECOVER’—investigators used the Functional Independence Measure (FIM), the Short-Form 36, a 6-minute walking test and Medical Research Counsel score-muscle strength testing. The main findings were that young patients (aged 2 weeks) had the worst functional outcome. Young patients with a LOS >2 weeks, older patients with a LOS 2 weeks had a functional status in between the first two groups. Based on these results, the ‘Towards RECOVER’—researchers suggest that these age—and LOS cutoffs could be useful in resource planning and informing patients and their families about expected functional outcomes.